Positive electrode active material, positive electrode sheet, electrode assembly, battery cell, battery and electrical equipment
By covering the conductive shell in lithium iron phosphate material and controlling the resistivity ratio, the problem of easy damage to the surface of nickel-cobalt-manganese ternary material is solved, and the problem of rapid early capacity decay during the normal temperature cycle of battery cells is improved. , improves capacity retention rate.
Patent Information
- Application Number
- CN202211106932.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-09
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-09-09
AI Technical Summary
The existing positive electrode active materials mixed with lithium iron phosphate materials and nickel-cobalt-manganese ternary materials have rapidly decayed in the early stage during the normal temperature cycle, resulting in damage to the capacity of the battery cell during the middle and late stages.
By covering the conductive shell in the lithium iron phosphate material and controlling the resistivity ratio of the nickel-cobalt-manganese ternary material and lithium iron phosphate material under certain standards, the conductances of the two are more matched, thereby improving the nickel-cobalt-manganese ternary material. The problem of material surfaces being easily damaged.
It effectively improves the problem of rapid capacity decay in the early stage during the normal temperature cycle, and improves the capacity retention rate of battery cells in the middle and late stages.
Smart Images

Figure CN115939322B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular, to a positive electrode active material, a positive electrode sheet, an electrode assembly, a battery cell, a battery, and an electrical device. Background Art
[0002] The currently proposed mixed positive electrode active material of lithium iron phosphate material (LFP) and nickel-cobalt-manganese ternary material (NCM) has a rapid capacity decay in the early stage during the normal temperature cycle, resulting in the loss of capacity of the battery cell in the middle and late stages of the cycle. Summary of the invention
[0003] In view of the above problems, the present application provides a positive electrode active material, a positive electrode plate, an electrode assembly, a battery cell, a battery and an electrical device. The positive electrode active material can improve the problem of rapid early capacity decay during normal temperature cycling by mixing lithium iron phosphate material and nickel-cobalt-manganese ternary material.
[0004] The embodiment of the present application is implemented as follows:
[0005] In the first aspect, the present invention provides a positive electrode active material, including: a nickel-cobalt-manganese ternary material and a lithium iron phosphate material, wherein the nickel-cobalt-manganese ternary material is LiNi x Co y Mn z M1 1-x-y-z O2, x>0, y>0, z>0, 1-xyz≥0, M1 is selected from one or more of Zr, Al, Mg, Nb, Ti and Ba, the lithium iron phosphate material includes a lithium iron phosphate core and a conductive shell coated on the surface of the lithium iron phosphate core, the mass proportion of the conductive shell in the lithium iron phosphate material is greater than 0.2%, and the lithium iron phosphate core is LiFe m M2 n PO4, m>0, n≥0, M2 is selected from one or more of Mn, Ti, Mg, V, Cr, Zr, Nb and W, and the resistivity R1 of the nickel-cobalt-manganese ternary material and the resistivity R2 of the lithium iron phosphate material satisfy: R1 / R2≤60.
[0006] In the technical solution of the embodiment of the present application, the surface of the lithium iron phosphate core is coated with a conductive shell with a specific mass percentage to prevent excessive polarization from affecting the capacity. On this basis, the ratio of the resistivity R1 of the nickel-cobalt-manganese ternary material and the resistivity R2 of the lithium iron phosphate material is controlled under a certain standard, so that the conductivity of the lithium iron phosphate material and the nickel-cobalt-manganese ternary material is more matched, which can improve the phenomenon that the surface of the nickel-cobalt-manganese ternary material is easily damaged, thereby improving the problem of rapid capacity decay in the early stage during normal temperature cycling.
[0007] In some embodiments, R1 / R2≤20. In this embodiment, the ratio of the resistivity R1 of the nickel-cobalt-manganese ternary material to the resistivity R2 of the lithium iron phosphate material is controlled to a smaller standard, so that the conductivity of the lithium iron phosphate material and the nickel-cobalt-manganese ternary material is more matched, which is conducive to better improving the problem of rapid capacity decay in the early stage during normal temperature cycling.
[0008] In some embodiments, under the test pressure of 8 MPa at room temperature, at least one of the following conditions (a) and (b) is met: (a) R1 is 1000 Ω·m to 4000 Ω·m; (b) R2 is 100 Ω·m to 200 Ω·m. In this embodiment, the resistivity R1 of the nickel-cobalt-manganese ternary material and the resistivity R2 of the lithium iron phosphate material are each controlled within a specific range, which is convenient to implement and is conducive to the matching of the conductivity of the lithium iron phosphate material and the nickel-cobalt-manganese ternary material.
[0009] In some embodiments, the mass proportion of the nickel-cobalt-manganese ternary material in the positive electrode active material is 10% to 30%. In this embodiment, the nickel-cobalt-manganese ternary material has an appropriate mass proportion to avoid too little nickel-cobalt-manganese ternary material resulting in a small increase in energy density, while avoiding too much nickel-cobalt-manganese ternary material resulting in high cost.
[0010] In some embodiments, the nickel-cobalt-manganese ternary material is selected from one or more of small single crystal materials, quasi-single crystal materials and polycrystalline materials; the Dv50 of the small single crystal material is 0.5μm to 3μm; in the quasi-single crystal material, the Dv50 of the secondary particles is 6μm to 10μm, and the Dv50 of the primary particles is 300nm to 600nm; in the polycrystalline material, the Dv50 of the secondary particles is 6μm to 10μm, and the Dv50 of the primary particles is 300nm to 600nm. In this embodiment, a specific type of nickel-cobalt-manganese ternary material is selected, and compared with the conventional single crystal type nickel-cobalt-manganese ternary material, the ion conductivity is better, so that the conductivity of the nickel-cobalt-manganese ternary material and the lithium iron phosphate material is more matched, which is conducive to better improving the problem of rapid capacity decay in the early stage during normal temperature cycling.
[0011] In some embodiments, the Dv50 of the lithium iron phosphate material is 1 μm to 2 μm. In this embodiment, the lithium iron phosphate material has a suitable particle size. On the one hand, the particle size is required to be increased to a certain extent relative to the conventional level to avoid the lithium iron phosphate material particle size being too small to wrap the nickel-cobalt-manganese ternary material and cause over-discharge, which can reduce the contact between the lithium iron phosphate material and the nickel-cobalt-manganese ternary material, which is beneficial to suppress the over-discharge of the nickel-cobalt-manganese ternary material, thereby helping to better improve the problem of rapid capacity decay in the early stage during normal temperature cycling; on the other hand, the particle size requirement avoids the lithium iron phosphate material particle size being too large, resulting in excessive polarization and affecting the cycle stability.
[0012] In some embodiments, the conductive shell is made of carbon. In this embodiment, the carbon material used as the conductive shell has the advantages of low cost, convenient processing, and good conductive performance.
[0013] In some embodiments, the mass proportion of the conductive shell in the lithium iron phosphate material is 0.5% to 1.5%. In this embodiment, the conductive shell has a suitable mass proportion in the lithium iron phosphate material. On the one hand, the mass proportion is reduced to a certain extent relative to the conventional level, reducing the amount of electrons gathered on the surface of the nickel-cobalt-manganese ternary material, which is beneficial to inhibit the over-discharge of the nickel-cobalt-manganese ternary material, thereby helping to better improve the problem of rapid capacity decay in the early stage of the normal temperature cycle process, and at the same time, it also reduces the cost; on the other hand, it avoids the mass proportion being too low to cause the rate performance to deteriorate and the polarization to be too large, which affects the cycle stability.
[0014] In a second aspect, an embodiment of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector, wherein the positive electrode active material layer contains the positive electrode active material as described in the above embodiment.
[0015] In some embodiments, a conductive agent is distributed between the positive electrode active materials, and the mass proportion of the conductive agent in the positive electrode active material layer is 0.1% to 1%. In this embodiment, the conductive agent has a suitable mass proportion in the positive electrode active material layer, so that the positive electrode active material layer as a whole has suitable conductivity, which is conducive to maintaining the room temperature cycle stability of the battery cell.
[0016] In a third aspect, an embodiment of the present application provides an electrode assembly, comprising a negative electrode plate, a separator, and the positive electrode plate of the above embodiment arranged in sequence.
[0017] In a fourth aspect, an embodiment of the present application provides a battery cell, comprising a housing and the electrode assembly of the above embodiment; the electrode assembly is accommodated in the housing.
[0018] In a fifth aspect, an embodiment of the present application provides a battery, comprising a box and a battery cell of the above embodiment; the battery cell is accommodated in the box.
[0019] In a sixth aspect, an embodiment of the present application provides an electrical device, comprising a battery cell as in the above embodiment or a battery as in the above embodiment.
[0020] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 A schematic diagram of the structure of a vehicle provided in some embodiments of the present application;
[0023] Figure 2 An exploded view of a battery provided for some embodiments of the present application;
[0024] Figure 3 for Figure 2 An exploded view of a battery cell is shown;
[0025] Figure 4 A schematic diagram of a partial structure of an electrode assembly provided in some embodiments of the present application;
[0026] Figure 5 A schematic diagram of the partial structure of the positive electrode plate provided in some embodiments of the present application.
[0027] icon:
[0028] Vehicles 1000;
[0029] Battery 100; Controller 200; Motor 300;
[0030] Box body 10; first part 11; second part 12; accommodating space 13;
[0031] Battery cell 20; housing 21; electrode assembly 22; electrode terminal 23; pressure relief structure 24;
[0032] Shell 211; cover 212; positive electrode sheet 221; negative electrode sheet 222; isolation film 223;
[0033] Positive electrode current collector 2211; Positive electrode active material layer 2212;
[0034] Negative electrode current collector 2221 ; Negative electrode active material layer 2222 . DETAILED DESCRIPTION
[0035] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0036] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0038] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0039] In the description of the embodiments of the present application, the orientations or positional relationships indicated by the technical terms "inside" and "outside" are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, rather than indicating or implying that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present application.
[0040] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral one; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present application can be understood according to specific circumstances.
[0041] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0042] In the embodiments of the present application, the same reference numerals represent the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments. It should be understood that the heights, lengths, widths, and other dimensions of the various components in the embodiments of the present application shown in the drawings, as well as the overall heights, lengths, widths, and other dimensions of the integrated device are only exemplary descriptions and should not constitute any limitation to the present application.
[0043] At present, from the perspective of market development, the application of power batteries is becoming more and more extensive. Power batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as military equipment and aerospace and other fields. With the continuous expansion of the application field of power batteries, the market demand is also constantly expanding.
[0044] In the current design of positive electrode active materials, in order to take into account the discharge specific capacity, energy density and safety performance, active materials with high discharge specific capacity and active materials with high safety performance are usually mixed.
[0045] In some current designs, nickel cobalt aluminum oxide (NCA) is used as the main material, and lithium iron phosphate is adsorbed on the surface of the nickel cobalt aluminum oxide material. The good safety and cycle performance of lithium iron phosphate material are used to make up for the poor safety of the nickel cobalt aluminum oxide material, while maintaining the high discharge specific capacity of the nickel cobalt aluminum oxide material. However, in this design, the lithium iron phosphate material is equivalent to the coating layer on the surface of the nickel cobalt aluminum oxide material, isolating the nickel cobalt aluminum oxide material from direct contact with the electrolyte and air, which will lead to a sacrifice in energy density.
[0046] In order to improve the above problems, in some other current designs, specific types of active materials are selected for direct mixing, for example, lithium iron phosphate material and nickel-cobalt-manganese ternary material are mixed to better balance energy density and safety performance.
[0047] However, the positive electrode active material currently proposed as a mixture of lithium iron phosphate material and nickel-cobalt-manganese ternary material has a rapid capacity decay in the early stage during the normal temperature cycle process, resulting in the loss of capacity of the battery cell in the middle and late stages of the cycle.
[0048] The applicant noted that during the normal temperature cycle process, the surface of the nickel-cobalt-manganese ternary material is easily damaged, resulting in rapid capacity decay in the early stage, and the capacity decay rate gradually stabilized after 200 to 300 cycles.
[0049] After further research by the applicant, it was found that the resistivity of commonly used lithium iron phosphate materials is between 10Ω·m and 50Ω·m, while the resistivity of commonly used nickel-cobalt-manganese ternary materials is above 10000Ω·m. The main reason why the surface of the nickel-cobalt-manganese ternary material is easily damaged is that the conductivity of the lithium iron phosphate material and the nickel-cobalt-manganese ternary material does not match. During the normal temperature cycle process, the current distribution of the nickel-cobalt-manganese ternary material is larger, and electrons gather on the surface of the nickel-cobalt-manganese ternary material. At the end of the discharge, the nickel-cobalt-manganese ternary material is over-discharged, which makes the surface of the nickel-cobalt-manganese ternary material easily damaged.
[0050] Based on this, in order to improve the above-mentioned problems, the present application proposes a positive electrode active material, which reasonably adjusts the conductivity of the lithium iron phosphate material and the nickel-cobalt-manganese ternary material when the lithium iron phosphate material and the nickel-cobalt-manganese ternary material are mixed, thereby improving the phenomenon that the surface of the nickel-cobalt-manganese ternary material is easily damaged, thereby improving the problem of rapid early capacity decay during normal temperature cycling.
[0051] For the convenience of description, the following embodiments are described by taking a vehicle as an example of an electrical device in an embodiment of the present application.
[0052] See also Figure 1 , see Figure 1 , Figure 1 A schematic diagram of the structure of a vehicle 1000 provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 100 is provided inside the vehicle 1000, and the battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The battery 100 may be used to power the vehicle 1000, for example, the battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300, and the controller 200 is used to control the battery 100 to power the motor 300, for example, for starting, navigating and driving the vehicle 1000.
[0053] In some embodiments of the present application, the battery 100 can not only serve as an operating power source for the vehicle 1000, but also serve as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.
[0054] In the present application, a battery 100 refers to a single physical module including one or more battery cells 20 to provide higher voltage and capacity. The battery 100 generally includes a housing 10 for encapsulating one or more battery cells 20. The housing 10 can prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells 20.
[0055] See also Figure 2 , Figure 2The exploded diagram of the battery 100 provided in some embodiments of the present application, the battery 100 may include a box body 10 and a battery cell 20, and the battery cell 20 is accommodated in the box body 10. Among them, the box body 10 is used to accommodate the battery cell 20, and the box body 10 can be a variety of structures. In some embodiments, the box body 10 may include a first part 11 and a second part 12, the first part 11 and the second part 12 cover each other, and the first part 11 and the second part 12 jointly define a receiving space 13 for accommodating the battery cell 20. The second part 12 may be a hollow structure with one end open, the first part 11 is a plate-like structure, and the first part 11 covers the open side of the second part 12 to form a box body 10 with a receiving space 13; the first part 11 and the second part 12 may also be hollow structures with one side open, and the open side of the first part 11 covers the open side of the second part 12 to form a box body 10 with a receiving space 13. Of course, the first part 11 and the second part 12 may be a variety of shapes, such as a cylinder, a cuboid, etc.
[0056] In the battery 100, there can be one or more battery cells 20. If there are more than one battery cell 20, the multiple battery cells 20 can be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 20 are both connected in series and in parallel. The multiple battery cells 20 can be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 20 is accommodated in the box 10. Alternatively, multiple battery cells 20 can be connected in series, in parallel, or in a mixed connection to form a module, and the multiple modules are then connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 10. The battery 100 may also include other structures. For example, the multiple battery cells 20 can be electrically connected through a busbar component to achieve parallel, series, or mixed connection of the multiple battery cells 20.
[0057] Each battery cell 20 may be a secondary battery 100 or a primary battery 100 ; it may also be a lithium-sulfur battery 100 , a sodium-ion battery 100 or a magnesium-ion battery 100 , but is not limited thereto.
[0058] See also Figure 3 , Figure 3 for Figure 2 The exploded view of the battery cell 20 is shown. The battery cell 20 refers to the smallest unit constituting the battery 100. The battery cell 20 may include a housing 21, an electrode assembly 22 and an electrolyte, and the electrode assembly 22 and the electrolyte are both contained in the housing 21.
[0059] The housing 21 may include a shell 211 and a cover 212. The shell 211 is a component used to cooperate with the cover 212 to form an internal sealed space of the battery cell 20, wherein the formed sealed space can be used to accommodate the electrode assembly 22, electrolyte and other components. The cover 212 refers to a component that covers the opening of the shell 211 to isolate the internal environment of the battery cell 20 from the external environment. The shape of the cover 212 can be adapted to the shape of the shell 211 to cooperate with the shell 211, and the cover 212 may also be provided with functional components such as electrode terminals 23 and pressure relief structures 24. A sealing ring may be configured between the opening of the shell 211 and the cover 212 to achieve sealing between the shell 211 and the cover 212.
[0060] The shell 211 and the cover 212 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shapes of the shell 211 and the cover 212 can be determined according to the specific shape and size of the electrode assembly 22. The shell 211 and the cover 212 can be made of various materials, such as but not limited to metals such as copper, iron, aluminum, stainless steel, and aluminum alloy. The sealing ring can be made of various materials, such as but not limited to PP (polypropylene), PC (polycarbonate), PET (polyethylene terephthalate) and other materials that are resistant to electrolyte corrosion, high toughness and fatigue resistance. A coating can be formed on the outer surface of the shell 211, and the material of the coating can be various, such as but not limited to corrosion-resistant materials such as Ni and Cr.
[0061] See also Figure 4 The electrode assembly 22 may be composed of a positive electrode sheet 221, a negative electrode sheet 222 and a separator 223. The battery cell 20 mainly relies on the movement of metal ions between the positive electrode sheet 221 and the negative electrode sheet 222 to work. The material of the separator 223 may be PP (polypropylene) or PE (polyethylene). Figure 5 The positive electrode sheet 221 includes a positive electrode current collector 2211 and a positive electrode active material layer 2212. Taking the lithium-ion battery cell 20 as an example, the material of the positive electrode current collector 2211 can be aluminum, and the main component of the positive electrode active material layer 2212 is the positive electrode active material. The negative electrode sheet 222 includes a negative electrode current collector 2221 and a negative electrode active material layer 2222. The material of the negative electrode current collector 2221 can be copper, and the negative electrode active material in the negative electrode active material layer 2222 can be carbon, silicon, etc. In addition, the electrode assembly 22 can be a winding structure or a laminated structure, and the embodiments of the present application are not limited thereto.
[0062] Next, the positive electrode active material proposed in the embodiments of the present application is described in detail.
[0063] In the first aspect, the present invention provides a positive electrode active material, including: a nickel-cobalt-manganese ternary material and a lithium iron phosphate material, wherein the nickel-cobalt-manganese ternary material is LiNi x Co y Mn z M1 1-x-y-z O2, x>0, y>0, z>0, 1-xyz≥0, M1 is selected from one or more of Zr, Al, Mg, Nb, Ti and Ba, the lithium iron phosphate material includes a lithium iron phosphate core and a conductive shell 211 coated on the surface of the lithium iron phosphate core, the mass proportion of the conductive shell 211 in the lithium iron phosphate material is greater than 0.2%, and the lithium iron phosphate core is LiFe m M2 n PO4, m>0, n≥0, M2 is selected from one or more of Mn, Ti, Mg, V, Cr, Zr, Nb and W, and the resistivity R1 of the nickel-cobalt-manganese ternary material and the resistivity R2 of the lithium iron phosphate material satisfy: R1 / R2≤60.
[0064] The lithium iron phosphate material has a core-shell structure, wherein the lithium iron phosphate core is the core part made of lithium iron phosphate as the main material, and the conductive shell 211 is the shell 211 part made of conductive material as the main material. The conductive shell 211 can completely cover the lithium iron phosphate core or partially cover the lithium iron phosphate core.
[0065] In the present application, the resistivity test method may adopt a test method known in the art. As an example, the test method includes: weighing a certain mass of powder sample, adjusting the depth of the feeding chamber, adding the sample to the feeding chamber, applying pressure at room temperature, the pressure value is selected from 4MPa, 8MPa, 12MPa and 16MPa, recording the powder resistivity test results at different pressure points, and the test range is <100000Ω·m.
[0066] As an example, the ratio of R1 / R2 satisfies, for example but not limited to: ≤60, ≤50, ≤45, ≤40, ≤35, ≤30, ≤25 or ≤20.
[0067] In the technical solution of the embodiment of the present application, the surface of the lithium iron phosphate core is coated with a conductive shell 211 with a specific mass percentage to prevent excessive polarization from affecting the capacity. On this basis, the ratio of the resistivity R1 of the nickel-cobalt-manganese ternary material and the resistivity R2 of the lithium iron phosphate material is controlled under a certain standard, so that the conductivity of the lithium iron phosphate material and the nickel-cobalt-manganese ternary material is more matched, which can improve the phenomenon that the surface of the nickel-cobalt-manganese ternary material is easily damaged, thereby improving the problem of rapid capacity decay in the early stage during normal temperature cycling.
[0068] In some embodiments, R1 / R2≤20.
[0069] In this embodiment, the ratio of the resistivity R1 of the nickel-cobalt-manganese ternary material to the resistivity R2 of the lithium iron phosphate material is controlled to a smaller standard, so that the conductivity of the lithium iron phosphate material and the nickel-cobalt-manganese ternary material are more matched, which is conducive to better improving the problem of rapid early capacity decay during normal temperature cycling.
[0070] In some embodiments, under normal temperature test conditions with a test pressure of 8 MPa, at least one of the following conditions (a) and (b) is met; (a) R1 is 1000Ω·m to 4000Ω·m; (b) R2 is 100Ω·m to 200Ω·m.
[0071] As an example, the value of R1 is, for example but not limited to, any one of 1000Ω·m, 1500Ω·m, 2000Ω·m, 2500Ω·m, 3000Ω·m, 3500Ω·m and 4000Ω·m, or a range between any two of them.
[0072] As an example, the value of R2 is, for example but not limited to, any one of 100Ω·m, 110Ω·m, 120Ω·m, 130Ω·m, 140Ω·m, 150Ω·m, 160Ω·m, 170Ω·m, 180Ω·m, 190Ω·m and 200Ω·m, or a range between any two of them.
[0073] In this embodiment, the resistivity R1 of the nickel-cobalt-manganese ternary material and the resistivity R2 of the lithium iron phosphate material are each controlled within a specific range, which is convenient to implement and is beneficial to the matching of the conductivity of the lithium iron phosphate material and the nickel-cobalt-manganese ternary material.
[0074] In some embodiments, the mass percentage of the nickel-cobalt-manganese ternary material in the positive electrode active material is 10% to 30%.
[0075] As an example, the mass proportion of the nickel-cobalt-manganese ternary material in the positive electrode active material is, for example but not limited to, any one of 10%, 15%, 20%, 25% and 30%, or a range between any two of them.
[0076] In this embodiment, the nickel-cobalt-manganese ternary material has an appropriate mass ratio, which avoids too little nickel-cobalt-manganese ternary material resulting in a small increase in energy density, and at the same time avoids too much nickel-cobalt-manganese ternary material resulting in higher costs.
[0077] In some embodiments, the nickel-cobalt-manganese ternary material is selected from one or more of small single crystal materials, quasi-single crystal materials and polycrystalline materials; the Dv50 of the small single crystal material is 0.5μm~3μm; in the quasi-single crystal material, the Dv50 of the secondary particles is 6μm~10μm, and the Dv50 of the primary particles is 300nm~600nm; in the polycrystalline material, the Dv50 of the secondary particles is 6μm~10μm, and the Dv50 of the primary particles is 300nm~600nm.
[0078] Small single crystal material refers to a single crystal material that meets the above-mentioned small particle size standard, and single crystal material refers to a material composed of a single crystal.
[0079] Quasi-single crystal materials refer to crystalline materials that are close to single crystals with large crystal size and small number of grains.
[0080] Polycrystalline materials are materials composed of randomly oriented grains that may have texture characteristics.
[0081] Dv50 represents the particle size corresponding to 50% of the volume distribution.
[0082] When the crystals are very small, due to the large surface energy of the grains, the small grains are easily combined together due to weak interaction forces, resulting in agglomeration between the grains, that is, many small grains gather together to form larger particles. Among them, the small grains before agglomeration are primary particles, and the larger particles formed after agglomeration are secondary particles.
[0083] As an example, Dv50 of the small single crystal material is, for example but not limited to, any one of 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm and 3 μm, or a range of values between any two of them.
[0084] As an example, the Dv50 of the secondary particles of the single-crystal-like material and the polycrystalline material may be, for example but not limited to, any point value among 6μm, 7μm, 8μm, 9μm and 10μm, or a range value between any two of them; the Dv50 of the primary particles of the single-crystal-like material and the polycrystalline material may be, for example but not limited to, any point value among 300nm, 400nm, 500nm and 600nm, or a range value between any two of them.
[0085] In this embodiment, a specific type of nickel-cobalt-manganese ternary material is selected. Compared with the conventional single crystal type nickel-cobalt-manganese ternary material, the ionic conductivity performance is better, so that the conductivity of the nickel-cobalt-manganese ternary material and the lithium iron phosphate material are more matched, which is conducive to better improving the problem of rapid early capacity decay during normal temperature cycling.
[0086] In some embodiments, the Dv50 of the lithium iron phosphate material is 1 μm to 2 μm.
[0087] As an example, the Dv50 of the lithium iron phosphate material is, for example but not limited to, any point value among 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm and 2μm, or a range value between any two of them.
[0088] In this embodiment, the lithium iron phosphate material has a suitable particle size. On the one hand, the particle size is required to be increased to a certain extent relative to the conventional level to avoid the lithium iron phosphate material particle size being too small and wrapping the nickel-cobalt-manganese ternary material and causing over-discharge. It can reduce the contact between the lithium iron phosphate material and the nickel-cobalt-manganese ternary material, which is beneficial to suppress the over-discharge of the nickel-cobalt-manganese ternary material, thereby helping to better improve the problem of rapid early capacity decay during normal temperature cycling. On the other hand, the particle size requirement avoids the lithium iron phosphate material particle size being too large, resulting in excessive polarization and affecting the cycle stability.
[0089] In some embodiments, the material of the conductive housing 211 is carbon.
[0090] In this embodiment, carbon material is used as the conductive shell 211, which has the advantages of low cost, convenient processing, and good conductive performance.
[0091] In some embodiments, the mass proportion of the conductive shell 211 in the lithium iron phosphate material is 0.5% to 1.5%.
[0092] As an example, the mass proportion of the conductive shell 211 in the lithium iron phosphate material is, for example but not limited to, any one of 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4% and 1.5%, or a range between any two of them.
[0093] In this embodiment, the conductive shell 211 has a suitable mass ratio in the lithium iron phosphate material. On the one hand, the mass ratio is reduced to a certain extent compared with the conventional level, which reduces the amount of electrons gathered on the surface of the nickel-cobalt-manganese ternary material, and is beneficial to inhibiting the over-discharge of the nickel-cobalt-manganese ternary material, thereby helping to better improve the problem of rapid capacity decay in the early stage of the normal temperature cycle process, while also reducing costs; on the other hand, it avoids the mass ratio being too low, resulting in deterioration of rate performance and excessive polarization that affects cycle stability.
[0094] See also Figure 5 In the second aspect, an embodiment of the present application provides a positive electrode plate 221, including a positive electrode collector 2211 and a positive electrode active material layer 2212 located on at least one side surface of the positive electrode collector 2211, wherein the positive electrode active material layer 2212 contains the positive electrode active material as described in the above embodiment.
[0095] In some embodiments, a conductive agent is distributed between the positive electrode active materials, and the mass proportion of the conductive agent in the positive electrode active material layer 2212 is 0.1% to 1%.
[0096] As an example, the mass proportion of the conductive agent in the positive electrode active material layer 2212 is, for example but not limited to, any point value among 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% and 1%, or a range value between any two of them.
[0097] In this embodiment, the conductive agent has a suitable mass ratio in the positive electrode active material layer 2212 , so that the positive electrode active material layer 2212 as a whole has suitable conductivity, which is beneficial to maintaining the room temperature cycle stability of the battery cell 20 .
[0098] See also Figure 4 In a third aspect, an embodiment of the present application provides an electrode assembly 22, comprising a negative electrode plate 222, a separator 223 and the positive electrode plate 221 of the above embodiment arranged in sequence.
[0099] See also Figure 3 In a fourth aspect, an embodiment of the present application provides a battery cell 20 , comprising a housing 21 and an electrode assembly 22 of the above embodiment; the electrode assembly 22 is accommodated in the housing 21 .
[0100] See also Figure 2 In a fifth aspect, an embodiment of the present application provides a battery 100 , comprising a housing 10 and a battery cell 20 of the above embodiment; the battery cell 20 is accommodated in the housing 10 .
[0101] In a sixth aspect, an embodiment of the present application provides an electrical device, such as a vehicle 1000, comprising a battery cell 20 as in the above embodiment or a battery 100 as in the above embodiment.
[0102] According to some embodiments of the present application, R1 / R2≤20; the nickel-cobalt-manganese ternary material is selected from one of a small single crystal material, a quasi-single crystal material and a polycrystalline material; the material of the conductive shell 211 is carbon, and the mass proportion of the conductive shell 211 in the lithium iron phosphate material is 0.5% to 1.5%.
[0103] Some specific embodiments are listed below to better illustrate the present application.
[0104] 1. Preparation of battery cells
[0105] (1) Preparation of negative electrode sheet
[0106] The negative electrode active material graphite, the conductive agent acetylene black, the binder styrene butadiene rubber, and the thickener sodium carboxymethyl cellulose are mixed in a weight ratio of 95:2:2:1, and an appropriate amount of deionized water is added and stirred to form a uniform negative electrode slurry; after the negative electrode slurry is coated on the negative electrode current collector copper foil, it is dried and cold pressed to obtain a negative electrode sheet.
[0107] (2) Preparation of positive electrode sheet
[0108] The positive electrode active material and (conductive agent + binder) are mixed in a mass ratio of 95:5, and dispersed in a solvent to obtain a positive electrode slurry; the positive electrode slurry is coated on a positive electrode current collector aluminum foil, and then dried and cold pressed to obtain a positive electrode sheet.
[0109] (3) Preparation of electrolyte
[0110] The electrolytes were prepared according to the following method:
[0111] In an argon atmosphere glove box with a water content of <10ppm, a certain mass of fully dried lithium salt LiPF6 is dissolved in a mixed solvent, and then an inorganic lithium salt additive is added thereto and stirred evenly to obtain an electrolyte.
[0112] (4) Preparation of batteries
[0113] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried outer packaging foil, and then after vacuum packaging, standing, forming, shaping and other processes, a battery cell is obtained.
[0114] 2. Test battery cells
[0115] Detection method:
[0116] Material resistivity test: Weigh a certain mass of powder sample, adjust the depth of the feeding chamber, add the sample into the feeding chamber, apply pressure at room temperature, the pressure value is 8MPa, record the powder resistivity test results at different pressure points, the test range is <100000Ω·m.
[0117] Battery cell cycle performance test: At 25 / 45℃, the battery cell is first charged to 4.3V at a constant current of 1C, then further charged to a current of 0.05C at a constant voltage of 4.3V, and then discharged to 3V at a constant current of 1C. This is a charge and discharge cycle process, and the discharge capacity this time is the discharge capacity of the first cycle. The battery cell is subjected to multiple cycle charge and discharge tests in the above manner, and the discharge capacity of the 200th cycle is detected, and the capacity retention rate of the battery after the cycle is calculated by the following formula 1.
[0118] Formula 1: Capacity retention rate of battery after 200 cycles (%) = (discharge capacity at the 200th cycle / discharge capacity at the 1st cycle) × 100%.
[0119] The performance parameters of the nickel-cobalt-manganese ternary material and lithium iron phosphate material in the positive electrode active materials used in each experiment are shown in Table 1, the parameter conditions of the battery cells in each experiment are shown in Table 2, and the cycle performance test results of the battery cells in each experiment are shown in Table 3.
[0120] Table 1.
[0121]
[0122]
[0123] Among them, for materials other than single-crystal-like materials and multi-single-crystal materials, Dv50 is understood according to the conventional particle size, that is, Dv50 is relative to the material as a whole, and does not distinguish between primary particles and secondary particles; for single-crystal-like materials and multi-single-crystal materials, Dv50 refers to the Dv50 of secondary particles, and the primary particle size refers to the Dv50 of primary particles.
[0124] Table 2.
[0125]
[0126]
[0127] The conductive agent ratio refers to the mass ratio of the conductive agent in the positive electrode active material layer. In Experiment 11, since the resistivity R2 of the lithium iron phosphate material exceeded the measurement range and no specific value was obtained, the specific ratio of R1 / R2 is not shown.
[0128] Table 3.
[0129]
[0130]
[0131] According to Tables 1 to 3, we can see that:
[0132] Compared with Experiment 1, Experiments 2 to 4 replaced the type of nickel-cobalt-manganese ternary material from conventional single crystal to one of small single crystal material, quasi-single crystal material and polycrystalline material. R1 / R2 was reduced, the room temperature cycle stability of the battery cell was better, the capacity attenuation in the early stage was improved, and the capacity retention rate was improved.
[0133] Compared with Experiment 1, the amount of carbon coating in the lithium iron phosphate material is different in Experiments 5 to 8. From the comparison between Experiments 5 to 7 and Experiment 1, it can be seen that by appropriately reducing the amount of carbon coating in the lithium iron phosphate material, R1 / R2 is reduced, the normal temperature cycle stability of the battery cell is better, the capacity attenuation in the early stage is improved, and the capacity retention rate is improved. From the comparison between Experiment 8 and Experiment 1, it can be seen that if the amount of carbon coating in the lithium iron phosphate material is too low, R1 / R2 is reduced, but due to excessive polarization, the normal temperature cycle stability of the battery cell has a certain decline, the capacity attenuation in the early stage is slightly worse, and the capacity retention rate is slightly reduced.
[0134] Compared with Experiment 1, Experiment 9 shows that the surface of the lithium iron phosphate material is not coated with carbon. Due to excessive polarization, the capacity cannot be fully utilized, resulting in a significant reduction in the room temperature cycle stability of the battery cell. The capacity attenuation in the early stage is seriously deteriorated and the capacity retention rate is significantly reduced.
[0135] Compared with Experiment 1, Experiments 10-12 increased the particle size of the lithium iron phosphate material, reduced R1 / R2, and improved the room temperature cycle stability of the battery cell. The capacity decay in the early stage was improved and the capacity retention rate was improved. At the same time, from the comparison between Experiment 10 and Experiments 11-12, it can be seen that the particle size of the lithium iron phosphate material in Experiment 10 was too high, the polarization was too large, the stability of the battery cell at 45°C was reduced, the capacity decay in the early stage was worse, and the capacity retention rate was reduced.
[0136] Compared with Experiment 1, Experiment 13 reduced the particle size of the lithium iron phosphate material, increased R1 / R2, reduced the room temperature cycle stability of the battery cell, worsened the early capacity attenuation, and reduced the capacity retention rate.
[0137] Compared with Experiment 6, Experiment 14 reduced the mass proportion of the conductive agent in the positive electrode active material layer, improved the room temperature cycle stability of the battery cell, improved the capacity attenuation in the early stage, and improved the capacity retention rate.
[0138] Compared with Experiment 6, Experiment 15 increased the mass proportion of the conductive agent in the positive electrode active material layer, the room temperature cycle stability of the battery cell decreased, the early capacity attenuation worsened, and the capacity retention rate decreased.
[0139] Compared with Experiment 1, Experiments 16 to 18 replaced the type of nickel-cobalt-manganese ternary material from conventional single crystal to one of small single crystal material, quasi-single crystal material and polycrystalline material, and at the same time appropriately reduced the amount of carbon coating in the lithium iron phosphate material. The room temperature cycle stability of the battery cell was significantly better, the capacity attenuation in the early stage was significantly improved, and the capacity retention rate was significantly improved.
[0140] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A positive electrode active material, characterized in that: It includes a nickel-cobalt-manganese ternary material and a lithium iron phosphate material, wherein the nickel-cobalt-manganese ternary material is LiNi x Co y Mn z M1 1-x-y-z O2, x>0, y>0, z>0, 1-xyz≥0, M1 is selected from one or more of Zr, Al, Mg, Nb, Ti and Ba, the lithium iron phosphate material comprises a lithium iron phosphate core and a conductive shell coated on the surface of the lithium iron phosphate core, the material of the conductive shell comprises a conductive material, the mass proportion of the conductive shell in the lithium iron phosphate material is greater than 0.2%, and the lithium iron phosphate core is LiFe m M2 n PO4, m>0, n≥0, M2 is selected from one or more of Mn, Ti, Mg, V, Cr, Zr, Nb and W, and the resistivity R1 of the nickel-cobalt-manganese ternary material and the resistivity R2 of the lithium iron phosphate material satisfy: R1 / R2≤60.
2. The positive electrode active material according to claim 1, characterized in that R1 / R2≤20.
3. The positive electrode active material according to claim 1, characterized in that Under normal temperature test conditions with a test pressure of 8 MPa, at least one of the following conditions (a) and (b) is met; (a) R1 is 1000Ω·m~4000Ω·m; (b) R2 is 100Ω·m~200Ω·m.
4. The positive electrode active material according to claim 1, characterized in that The mass proportion of the nickel-cobalt-manganese ternary material in the positive electrode active material is 10% to 30%.
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that The nickel-cobalt-manganese ternary material is selected from one or more of small single crystal materials, quasi-single crystal materials and polycrystalline materials; The Dv50 of the small single crystal material is 0.5 μm to 3 μm; In the quasi-single crystal material, the Dv50 of the secondary particles is 6 μm to 10 μm, and the Dv50 of the primary particles is 300 nm to 600 nm; In the polycrystalline material, the Dv50 of the secondary particles is 6 μm to 10 μm, and the Dv50 of the primary particles is 300 nm to 600 nm.
6. The positive electrode active material according to any one of claims 1 to 4, characterized in that The Dv50 of the lithium iron phosphate material is 1 μm to 2 μm.
7. The positive electrode active material according to any one of claims 1 to 4, characterized in that The conductive shell is made of carbon.
8. The positive electrode active material according to claim 7, characterized in that The mass proportion of the conductive shell in the lithium iron phosphate material is 0.5% to 1.5%.
9. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector, wherein the positive electrode active material layer contains the positive electrode active material according to any one of claims 1 to 8.
10. The positive electrode sheet according to claim 9, characterized in that: A conductive agent is distributed between the positive electrode active materials, and the mass proportion of the conductive agent in the positive electrode active material layer is 0.1% to 1%.
11. An electrode assembly, characterized in that: It comprises a negative electrode sheet, a separator and the positive electrode sheet as claimed in claim 10 which are arranged in sequence.
12. A battery cell, characterized in that: comprising a housing and the electrode assembly as claimed in claim 11; The electrode assembly is accommodated in the housing.
13. A battery, characterized in that: comprising a box body and a battery cell as claimed in claim 12; The battery cells are accommodated in the box.
14. An electrical device, characterized in that: Comprising the battery cell as claimed in claim 12 or the battery as claimed in claim 13.
Citation Information
Patent Citations
Positive electrode film and lithium ion power battery, and preparation method thereof
CN102956874A
Lithium ion battery positive pole, method for preparing same and lithium ion battery cell with lithium ion battery positive pole
CN109411751A